THE IMPORTANCE OF EPIC KNOWLEDGE IN BAKHSHI’S MEMORY (American Journal of Interdisciplinary Research and Development, 2023)
This article talks about epic consciousness, epic memory and epic knowledge in Uzbek folk epics, and focuses on the current state of Uzbek folk epic memory and epic knowledge.